Answer:
The solution of the inequality is:
[tex]x>2[/tex]
Step-by-step explanation:
Given inequality:
[tex]-1 >-2(x - 4)-5(4x-7)[/tex]
Solving the inequality.
Using distribution.
⇒ [tex]-1 >(-2x) +((- 4)(-2))+(-5\times4x)+((-5)(-7))[/tex]
⇒ [tex]-1 >-2x +8-20x+35[/tex]
Combining like terms
⇒ [tex]-1 >-2x-20x+35+8[/tex]
⇒ [tex]-1 >-22x +43[/tex]
Adding [tex]22x[/tex] both sides.
⇒ [tex]-1+22x >-22x +43+22x[/tex]
⇒ [tex]-1 +22x> 43[/tex]
Adding 1 both sides.
⇒ [tex]-1+1 +22x> 43+1[/tex]
⇒ [tex]22x>44[/tex]
Dividing both sides by 22.
⇒ [tex]\frac{22x}{22}>\frac{44}{22}[/tex]
⇒ [tex]x>2[/tex]
Thus, the solution of the inequality is:
[tex]x>2[/tex]